ON THE LEXEME XA OR XIA AND ITS RELATIONSHIP WITH THE NUMERALS OF THE MOCHICA LANGUAGE - Salas Garcia, José Antonio (2011)
This article discusses a passage of a recent article by Quilter et alia (2010), where there is a reference to the Mochica numbering system, and where Hovdhaugen is cited as an authority for an analysis of two alleged suffixes recursively used in the numbering of this language. What we propose in this paper is to prove that the observation of Quilter et alia is wrong with respect to an alternative basis to the decimal numbers in the Mochica numbering system, and with respect to Hovdhaugen’s proposal, there are are not two suffixes, but a unique lexeme. To prove our assertions, we reviewed the basic concepts in a numeral system and checked out all the contexts in which these allged prefixes appear, providing evidence for a different analysis.